The Reality of Tense - Richter, Stefanie (Hamburg University Press, 2004)
philosophical jargon are called Tenses". To claim that Tenses are real is to claim that they are satisfied, i.e. that something in fact possesses them. The debate between realists and antirealists concerning Tense has so far been conducted in ontological terms. Realists about Tense (so-called A-theorists)claim that things really do have Tenses, antirealists (Btheorists) deny this. Most of them claim that Tenses can be reduced to tenseless properties. This book criticises the current debate between A-theorists like Quentin Smith and B-theorists like D. H. Mellor on methodological grounds. It suggests an alternative strategy for how the debate might proceed, where insights from other kinds of realism-debates are made useful for the debate about Tense. This book makes the original attempt to apply two general frameworks for realism-debates, developed by Michael Dummett and Crispin Wright, to the debate about Tense. Here the focus lies on the correct interpretation of the truth-predicate for statements of the disputed kind. The aim of this publication is to show that the debate about the reality of Tense should be reinterpreted as a debate about the truth and semantics of statements which ascribe Tenses."